A Study of Determinants of Low Birth Weight in Newborns Delivered at One of The Tertiary Care Hospitals in Saurashtra Region, Gujarat - Harsh Patel; Jitesh Mehta; Rohitkumar Ram; Dipesh Parmar (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Birth weight is one of the most important criteria for determining neonatal and infant survival and is considered a sensitive index of the nation's health and development. The World Health Organization (WHO) defines low birth weight (LBW) as "Birth weight less than 2500 grams" regardless of gestational age, the measurement being taken preferably within the first hour of life. Objectives:1)To estimate the prevalence of LBW among sample population at tertiary care hospital.2)To study the distribution of newborns, according to socio-demographic characteristics of the mother and its association with LBW. Method: A hospital based cross-sectional study was carried out among 500 newborns between December 2020 and November 2021. Participants were selected by systematic random sampling technique. The data were collected from the case file and face-to-face interview. Both descriptive and inferential statistics were used in the analysis. Results: Prevalence of low birth weight was 29.2%. Majority 271 (54.2%) of newborn mothers'age group was between 21 to 25 years. More than half 272 (54.4%) newborns were from mothers who studied up to primary level education and more than three forth 389 (77.8%) were from mothers who were housewives. Majority 293 (58.6%) of newborns were from the urban area, around three forth 382 (76.4%) newborns were Hindu andnearly two fifth 194 (38.8%) newborns belonged to lower middle class. Prevalence of low birth weight was significantly higher in mothers aged>35 and ≤20, who were illiterate, doing labour work and belonging to lower socio-economic class. Conclusion: The prevalence of Low Birth Weight was 29.2% among sample population. Socio-demographic variables like maternal age >35 years and ≤20 years, illiteracy, labour work and lower socio-economic class had shown significant risk for delivering Low Birth Weight babies.